KECAKAPAN HIDUP PERSONAL DAN VOKASIONAL KAUM PEREMPUAN MELALUI TENUN BUNA BATU NONA DI RT/01 RW/01 KELURAHAN OESAPA - Taneo, Maria; Sogen, Yosephina K; Syukur, Abdul (Education For All, 2024)
The formulation of the problem in this study is how women's personal and professional life skills are enhanced by the Buna Batu Nona Weaving group. The purpose of this study was to identify the personal and professional life skills of women in the Buna Batu Nona weaving group. This research uses a descriptive qualitative approach. This research was conducted in the Buna Batu Nona Weaving group at RT/01 RW/01 Oesapa Village. A targeted sampling technique was used to identify the whistleblowers, which then identified three individuals, including a person responsible for the work area, a leader of the web group, and a member of the group. Data collection techniques used include observation, interviews, and documentation. The results of this study show that there are two (2) skills, namely personal life skills and professional life skills. Personal life skills have three indicators: 1. self-confidence, 2. rational/initiative thinking skills and 3. independence. Professional skills include the process of Buna weaving. Keywords: Buna Weaving, Group Personal and Professional Life Skills